Vybor Rossii . Vybor Rossii . Russia's Choice . Выбор России - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Presentation of the electoral bloc "Vybor Rossii" ("Russia's Choice"). Featured in the program: Gaidar, Egor Timurovich (First Deputy Prime Minister of the Russian Federation); Chubais, Anatolii Borisovich (Chairman of the Sate Committee on Property of the Russian Federation) Выступление избирательного блока "Выбор России.". В программе участвуют: Гайдар, Егор Тимурович (Первый заместитель председателя Правительства Российской Федерации); Чубайс, Анатолий Борисович (Председатель Государственного комитета по имуществу Российской Федерации.)